Kirkko, papisto ja yhteiskunta 1600-1800 - Viitaniemi, Ella (Historiallisia Tutkimuksia series., 2023)
It is generally recognized that in early modern society, the position of the church and clergy was very central. As many historians have stated over the decades, the church and state were closely connected and their power structures and ideologies supported each other. However, when studying the social and public role of the church and clergy, it soon becomes quite clear how pervasive this phenomenon was. The church not only created but also maintained and acted as a part of international, national, and local communities, structures, and cultures that connected people regardless of their social status and gender. The church was a spiritual, administrative, and social institution and experience environment, whose tasks, scope, and meanings changed and intertwined with the development, needs, and requirements of society. In this book, we investigate from different perspectives the motives and different means by which the church and clergy came to play a significant part in early modern society. In this volume, the church is considered both as an administrative institution and as a social space and cultural structure. Hence, we do not focus on the history of theology or doctrinal questions. Instead, we consider the social and public roles and meanings of the church. The church as such is understood in this book as transnational, a strong national and local institution, and also a space and structure. The church had its own institutionalized place in society and its activities and rights were defined by law (Church law 1696, the Law of the Swedish kingdom 1734) and by the decrees given by the Royal Majesty. The church had its own archbishop-led administrative organization under the Royal Majesty and it worked in close cooperation with the Crown administration and county governors. In this volume, we understand the clergy as church servants, a trained and appointed professional group, a separate estate (social class), and also as a wide social network constructed by their families. The approach of this book is social science history. In other words, the book examines the church and the clergy as an integral part of society and the individual communities who lived in the current Finnish territory during the early modern era. The topic is examined on the basis of three conceptual themes reflecting important new areas of research in the study of the social significance of the church and clergy: (1) the clergy and family as part of the community, (2) the church as a jointly built space, and (3) the church as an arena for interaction, knowledge, and politics. We approach this multidimensionality using different research questions, sources, methods, and theoretical approaches. The volume focuses on the 17th to 19th centuries, but many of the church and clergy-related phenomena are much older, and some of them extend to the present, so the articles also move beyond this time frame.